ANALISIS EFEKTIVITAS PELAKSANAAN KREDIT BERGULIR PADA PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERDESAAN DI KECAMATAN IMOGIRI DAN KECAMATAN SEWON KABUPATEN BANTUL TAHUN 2021 - Mujahid Amrudin (Jurnal Riset Daerah, 2023)
This research aims to analyze the effectiveness of implementing PNPM Mandiri Perdesaan revolving credit distribution in the 2021 period. The analysis used in this study is descriptive analysis, effectiveness analysis, and Strengths, Weaknesses, Opportunities, and Treaths (SWOT). The data used is primary data with a total of 30 respondents. The data used in this study came from a questionnaire given to revolving credit recipients. The results showed that the implementation of PNPM Mandiri Perdesaan revolving loans in Sewon and Imogiri sub-districts was effective and right on target